Comparison of mood state between team sports and individual sports among young athletes - Shazreen Dolleye Ladiun@Ledion (Penerbit Universiti Kebangsaan Malaysia, 2021)
The aim of this study was to compare the mood state between team sports and individual sports among young athletes. A total number of 279 (n=279) secondary school athletes who participated in Majlis Sukan Sekolah Daerah (MSSD) Tuaran, Sabah competition were recruited in the present study. The participants were asked to answer the Brunel of Mood Scale (BRUMS) one hour prior to the competition. Independent Sample T-Test were used to compare the mood state between team and individual sports among young athletes. Result showed higher mean of mood state in individual sports (M=1.22) as compared to team sports (M=1.19). There was a significant difference between team and individual sports on fatigue (p=.017) and confusion (p=.009), while there was no significant difference on depression (p=.296), tension (p=.565), vigour (p=.296) and anger (p=.79) among young athletes. Team sports shown significantly lower level of confusion as compared to individual sports, whereas fatigue is significantly higher in team sports as compared to individual sports.